Design and manufacture of information systems information system tracking people's business credit applications web-based information system at PT. Bank Rakyat Indonesia - Azis, Ibnu; Sharyanto, Sharyanto; Gunawan Sudarsono, Bernadus (Yayasan Bina Internusa Mabarindo, 2024)
Bank Rakyat Indonesia is one of the government-owned banks and has committed to providing the best service through a variety of products, including savings and loan products, as well as the People's Business Credit (KUR). However, there are problems related to the KUR application tracking process which is still manual, through short message communication, telephone calls, or direct visits to BRI offices. This system has not been computerized, causing customer assessments of Bank BRI to be poor. To handle these obstacles, a web-based KUR application tracking information system was created by modeling the system using the Unified Modeling Language (UML) and using the PHP programming language and MySQL as a database, so as to increase efficiency and customer satisfaction in using services at Bank BRI